2018
DOI: 10.1016/j.redox.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

miR-200a-5p regulates myocardial necroptosis induced by Se deficiency via targeting RNF11

Abstract: Necroptosis has been discovered as a new paradigm of cell death and may play a key role in heart disease and selenium (Se) deficiency. Hence, we detected the specific microRNA (miRNA) in response to Se-deficient heart using microRNAome analysis. For high-throughput sequencing using Se-deficient chicken cardiac tissue, we selected miR-200a-5p and its target gene ring finger protein 11 (RNF11) based on differential expression in cardiac tissue and confirmed the relationship between miR-200a-5p and RNF11 by dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 50 publications
3
70
0
Order By: Relevance
“…As shown in Figure A,B, compared to the control group, mitochondrial membrane potential was reduced to near‐normal levels. Interestingly, resveratrol treatment reversed mitochondrial membrane potential, as evidenced by increased red‐to‐green fluorescence ratio . Besides, mitochondrial function was also determined via measuring adenosine triphosphate (ATP) content in N2a cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure A,B, compared to the control group, mitochondrial membrane potential was reduced to near‐normal levels. Interestingly, resveratrol treatment reversed mitochondrial membrane potential, as evidenced by increased red‐to‐green fluorescence ratio . Besides, mitochondrial function was also determined via measuring adenosine triphosphate (ATP) content in N2a cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, resveratrol treatment reversed mitochondrial membrane potential, as evidenced by increased red-to-green fluorescence ratio. 59,60 Besides, mitochondrial function was also determined via measuring adenosine triphosphate (ATP) content in N2a cells. As shown in Figure 3C, compared to the control group, HR injury reduced ATP production in N2a cells, and this alteration could be reversed by high dose resveratrol.…”
Section: Resveratrol Modulates Mitochondrial Function and Energy Mementioning
confidence: 99%
“…Previous studies also indicate that miRNAs confer function through specific targeting of molecules correlated with necroptosis. For example, miR-200a-5p binds with ring finger protein 11 to trigger RIPK3dependent necroptosis in vivo and in vitro (22). However, it is unknown whether miRNAs modulate renal injury by directly targeting the central mediator of the necroptotic pathway, specifically MLKL.…”
Section: Discussionmentioning
confidence: 99%
“…According to Verjans, heart failure-associated down regulation of the miRNA-221/222 family enables fibrosis signaling in a pressure-overloaded heart in rats [12]. In our previous study, we showed in chickens that regulation of miR-200a-5p and its target gene blocks necroptosis in the heart, which revealed a novel myocardial necrosis regulation model in heart disease [13].…”
Section: Introductionmentioning
confidence: 94%